Dampak paparan radiasi sinar x lingkungan terhadap leukosit dari petugas radiologi - Aji, Pramudya Santoso; Mandagi, Ayik Mirayanti (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2023)
White blood cells are part of the hematopoetic system that is radiosensitive and are markers for determining the effects and intensity of ionizing radiation. This quantitative study aims to see the effect of ionizing radiation (x-rays) from x-ray services on the white blood cells of radiology officers at advanced health facilities in Pare District, Kediri Regency between September 2022, and January 2023. Using the slovin formula, a total of 60 participants were determined, 30 radiology nurses and 30 comparison groups of administrative officers. When viewed as a whole, the relative number of white blood cells there was no significant difference between the radiology officer group and the administrative officer, but the administrative officer group tended to have a a little higher white blood cell count. Significant differences occurred in the relative number of neutrophils with a significance of 0.0001 (0.05) Neutrophils of radiology officer tended to be smaller than the dissident group. The number of lymphocytes of radiology officer is different from administrative officer and tends to have higher count. Based on the findings it can be indicated if x-ray exposure affects the white blood cell count.